THE IMPACT OF PEER FEEDBACK ON HIGHER EDUCATION STUDENTS’ ORAL PRESENTATION: A CASE STUDY - Suharni, Suharni; Imelwaty, Sri; Sesmiyanti, Sesmiyanti; Perpisa, Lili (Universitas PGRI Sumatera Barat, 2022)
Peer feedback on oral presentation is still an unexplored area. Much research has been conducted on peer feedback in various teaching and learning contexts, only a few about how peer gives feedback on his/her partner’ oral presentations. The study described here focuses using peer feedback on oral presentations. Analyzing data from semi-structured interviews, this case study investigated impact of giving peer feedback on oral presentations used by English as Foreign Language (EFL) college students on other student’s oral presentation tasks. Data analysis revealed that the peer gave oral feedback mainly focused on content-related criteria (quality of introduction, structure, and conclusion). Most of the peers focused on the nature of the delivery (eye-contact, vocal delivery, enthusiasm, interaction with the audience and body-language), and a few focused on a general quality and on the design of the students’ PowerPoint (PPT) slides.